Scientific Research in the Antarctic Treaty System - Gozhik, P.F.; Gurzhiy, A.N.; Lytvynov, V.A. (Український антарктичний журнал, 2009)
The report highlights the most important initiatives put forward by SCAR in the Concept "Antarctic Science in the XXI century". Taking into consideration that the Antarctic Science becomes increasingly complex and expanding in the geographical dimension, in the XXI century the international cooperation and partnership will be required in areas, such as: Joint infrastructure and logistics; Expanding of the geographical presence; Joint research, technology, standardization of methods and measurement, international data bases and research results archives.